2017
DOI: 10.17816/ped815-26
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profile of Tears for the Diagnosis of Uveitis Associated with Juvenile Idiopathic Arthritis: Setting Targets to Achieve Results

Abstract: The paper presents epidemiologic and pathophysiological aspects of the problem statement for early recognition of Uveitis (Uv) associated with Juvenile Idiopathic Arthritis (JIA) in terms of the proteomic profile of tears as well as the results of an attempt to solve this problem by means of the Tandem Mass-Spectrometry (TMS). The solution of this problem is of the highest relevance due to revolutionary changes in treatment strategies after introducing highly effective biologics. Content analysis of literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…The investigation detected 1.224 unique protein groups, of which 120 were significantly different from healthy controls. Finally, in a study on tear proteome by Chunky et al, lactoferrin and lipocalin were identified as promising biomarkers for JIA-associated uveitis [7]. Nevertheless, there are no well-defined tear fluid biomarkers for AAU, let alone a consensus about their diagnostic value.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation detected 1.224 unique protein groups, of which 120 were significantly different from healthy controls. Finally, in a study on tear proteome by Chunky et al, lactoferrin and lipocalin were identified as promising biomarkers for JIA-associated uveitis [7]. Nevertheless, there are no well-defined tear fluid biomarkers for AAU, let alone a consensus about their diagnostic value.…”
Section: Introductionmentioning
confidence: 99%